Education Federalism and Minority Disproportionate Representation Monitoring: Examining IDEA Provisions, Regulations, and Judicial Trends. (December 2019) - Strassfeld, Natasha M.
States have been granted increasingly greater agency both to determine standards for minority disproportionate representation (MDR) monitoring in special education placements and to set the relevant cutoffs and sanctions when significant disproportionality is found. State authority has been bolstered by an education federalism framework, case law, and updated legislative and regulatory guidance under the Individuals with Disabilities Education Act. Using legislative and judicial analysis to both examine education federalism and its impact on state and federal authority and analyze the legislative history associated with MDR monitoring and recent judicial trends within federal case law regarding equal protection constitutional challenges brought by plaintiff parents and students with disabilities in MDR litigation, this article finds that states are increasingly granted greater authority from judicial opinions and policy to monitor states' practices. Legal and policy implications for stakeholders (e.g., parents, students, school districts) are also discussed.